Teacher qualities as perceived by the third and fourth year students of Mount Carmel High School -- its implications to in-service training - Villasin, Irene S. (Animo Repository, 1979)
This study was undertaken to rate the teachers' qualities as perceived by the third and fourth year students of Mount Carmel High School in the school year 1978-1979. The Purdue Rating Scale for Instructors was used. Objectively, the students were able to rate their teacher's qualities as they perceived them in the following traits: interest in the subject, sympathetic attitude towards the students, fairness in grading, liberal and progressive attitude, presentation of subject matter, sense of proportion and humor, self-reliance and confidence, personal peculiarities, personal appearance, stimulating intellectual curiosity. The ratings given by the students were then tallied and summarized. The formula for finding the mean for grouped data and the simple formula for finding the average mean was used. The result of this study led to the acceptance of the given assumptions as follows: 1. Students of the MCHS are an excellent source of information to determine and rate the teacher's qualities objectively 2. The teacher's qualities were shown measurable and 3. The students gave valid ratings with honesty and objectivity.